2021
DOI: 10.1186/s12870-021-03108-0
|View full text |Cite
|
Sign up to set email alerts
|

Transcriptomic analysis to reveal the differentially expressed miRNA targets and their miRNAs in response to Ralstonia solanacearum in ginger species

Abstract: Background Bacterial wilt is the most devastating disease in ginger caused by Ralstonia solanacearum. Even though ginger (Zingiber officinale) and mango ginger (Curcuma amada) are from the same family Zingiberaceae, the latter is resistant to R. solanacearum infection. MicroRNAs have been identified in many crops which regulates plant-pathogen interaction, either through silencing genes or by blocking mRNA translation. However, miRNA’s vital role and its targets in mango ginger in protecting ba… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(7 citation statements)
references
References 67 publications
0
6
0
Order By: Relevance
“…solanacearum infestation ( Hwang et al, 2011 ). Other plants such as Arabidopsis ( Zhao et al, 2019 ), tomato ( French et al, 2018 ), potato ( Zuluaga et al, 2015 ), ginger ( Snigdha and Prasath, 2021 ), and aubergine ( Chen et al, 2018 ) showed a similar situation after inoculation with R . solanacearum .…”
Section: Cell Wall Involvement In the Fight Against Ralston...mentioning
confidence: 85%
See 1 more Smart Citation
“…solanacearum infestation ( Hwang et al, 2011 ). Other plants such as Arabidopsis ( Zhao et al, 2019 ), tomato ( French et al, 2018 ), potato ( Zuluaga et al, 2015 ), ginger ( Snigdha and Prasath, 2021 ), and aubergine ( Chen et al, 2018 ) showed a similar situation after inoculation with R . solanacearum .…”
Section: Cell Wall Involvement In the Fight Against Ralston...mentioning
confidence: 85%
“…In pepper, genes associated with xylan biosynthesis and cell wall organization were significantly enriched in response to R. solanacearum infestation (Hwang et al, 2011). Other plants such as Arabidopsis (Zhao et al, 2019), tomato (French et al, 2018), potato (Zuluaga et al, 2015), ginger (Snigdha and Prasath, 2021), and aubergine (Chen et al, 2018) showed a similar situation after inoculation with R. solanacearum. All of this evidence suggests a role for the cell wall in defense against R. solanacearum infestation.…”
Section: Cell Wall Involvement In the Fight Against Ralstonia Solanac...mentioning
confidence: 95%
“…In the model plants, microRNA159 ( Ath - miR159 a,b,c) is a highly preserved miRNA in plants and contributes to stress responses [ 63 ]. Ath- miR5658 , Ath - miR858 , and Ath - miR1886 were also found to be responses to various stress tolerances [ 64 , 65 , 66 ]. In this work, we identified several miRNAs from Arabidopsis and P. patens that theoretically target overrepresented TF families in S. caninervis , similar to previous report s , stress-related miRNAs also target many TFs in S. caninervis , such as Ath-miR5658 potentially targeted four ScTF s members (Sc_ g03411_bHLH , Sc_g06422_ERF , and Sc_g02274_MYB ) and Ath-miR159 can specifically target Sc _ g13935_MYB.…”
Section: Discussionmentioning
confidence: 99%
“…lncRNA expression is cell-type- or tissue-specific, developmentally regulated, and may differ in response to numerous stimuli ( Derrien et al, 2012 ). miRNAs are a new class of small, non-coding RNAs (20–24 nucleotides in length) that regulate gene expression at the post-transcriptional level through mRNA cleavage or translational inhibition ( Snigdha and Prasath, 2021 ; Chandra et al, 2023 ). In recent years, the identification and functional analysis of plant miRNAs has become one of the hottest research areas in plant science due to their role in almost all biological and metabolic processes, including plant organ development, signaling pathways, disease, and stress responses ( Sun et al, 2012 ; Anjali et al, 2017 ; Chandra et al, 2023 ).…”
Section: Noncoding Rnas: Switch Guiding Switch Resourcesmentioning
confidence: 99%